3D-BIOPRINTING OF BONE TISSUE IN VITRO И IN SITU - Sultanova, D.; Batpen, A.; Saginova, D.; Akilbekova, D. (Eurasian Journal of Applied Biotechnology, 2024)
Advanced techniques in bone tissue regeneration include innovative achievements in the field of tissue engineering, among which 3D bioprinting technology holds a special place. This method demonstrates significant progress, driven by its numerous advantages, confirmed through extensive scientific research. 3D bioprinting offers the capability of precise printing of bone transplants with specified geometry, incorporating necessary biomaterials such as cells and growth factors, which facilitates effective osteoinduction, osteoconduction, and vascularization. This review article analyzes various modern methods of bone tissue restoration, including the use of autotransplants, allotransplants, and synthetic bone transplants. Particular attention is paid to the latest innovations in 3D bioprinting, opening prospects for creating individualized bone tissues characterized by a high degree of biocompatibility and minimizing the need for invasive procedures. Additionally, the article presents the concept of in situ bioprinting, developed by Weiss and his colleagues in 2007, as a method of direct printing of bio-inks directly in the area of damage in a living organism. This progressive approach provides high precision in the restoration of tissue defects, regardless of their complexity and geometric features. Over the last decade, several successful clinical cases of using printed structures have been registered, demonstrating the significance of 3D bioprinting in treating life-threatening diseases, as well as in accelerating the regeneration process and creating tissue transplants for subsequent implantation.